High-fat taste challenge reveals altered striatal response in women recovered from bulimia nervosa: A pilot study. (May 2014) - Radeloff, Daniel; Willmann, Kathrin; Otto, Lisa; Lindner, Michael; Putnam, Karen; Leeuwen, Sara Van; Kaye, Walter H; Poustka, Fritz; Wagner, Angela
Abstract Objectives. Individuals with anorexia nervosa (AN) and bulimia nervosa (BN) tend to have disordered thinking and eating behaviours in regards to fat containing foods. This is the first study to investigate neuronal pathways that may contribute to altered fat consumption in eating disordered patients. Methods. We used functional magnetic resonance imaging (fMRI) to compare responses to a high-fat cream stimulus, water, and a non-caloric viscous stimulus (CMC) to control for response to viscosity in individuals recovered from AN (N = 15), BN (N = 14) and a healthy control sample (CW, N = 18). Results. An interaction analysis (ANOVAR) comparing the three groups (AN, BN, CW) and the three conditions (cream, CMC, water) revealed significant differences in the left anterior ventral striatum (AVS). A post hoc analysis displayed a higher magnitude of response for the contrast cream/water in BN compared to AN or CW and for the contrast CMC/water in BN compared to AN. Conclusions. BN showed an exaggerated AVS response for the cream/water contrast in comparison to AN or CW. Moreover, BN showed an exaggerated AVS response for the CMC/water contrast in comparison to AN. These findings support the possibility that BN have an altered hedonic and/or motivational drive to consume fats.